DESIGN AND IMPLEMENTATION OF SOFTWARE-DEFINED DOPPLER RADAR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The subject of this article is a study of the possibility of practical implementation of a Doppler CW radar based on software-defined radio (SDR) technology. The paper presents overview of two technologies. Initially the architecture and basic characteristics of a Doppler CW radar are described, followed by an overview of SDR concept and types and characteristics of typical constructive elements for its realization.  Finally, a practical implementation by usage of USRP front-end and the GNU Radio Framework is presented. For the successful implementation of the Doppler CW radar architecture an additional amplifier is included. The material presents the results of tests performed using the practical implementation of a Doppler CW SDR radar, demonstrating the functionality of the implementation.